Tetraploid Induction and Establishment of Breeding Stocks for All-Triploid Seed Production - Huiping Yang; Ximing Guo; John Scarpa (EDIS)
Triploid-tetraploid breeding technology has been applied to commercial oyster aquaculture worldwide. Triploid oysters are becoming the preferred aquaculture product because of their fast growth, better meat quality, and year-round harvest. Tetraploids are essential for triploid oyster aquaculture because commercial production of all-triploid seed depends on the availability of tetraploids for reproductive materials. This 8-page fact sheet written by Huiping Yang, Ximing Guo, and John Scarpa and published by the UF/IFAS School of Forest Resources and Conservation, Program in Fisheries and Aquatic Sciences, conveys basic knowledge about tetraploid induction and breeding to commercial shellfish culturists and the general public. http://edis.ifas.ufl.edu/fa215